Organization management strategy for Generation Y performance sustainability - Mehtab Alam; Mudiarasan Kuppusamy (Cogent Business & Management, 2024)
This paper examines an under explored and integrated organization management strategy issue for the enhancement of the organizational performance. Considering two critical domains namely Human Resource and Organizational Development as theorised by this study is motivated by extend of the influence of those domains on the Generation Y staff of a GLC company in Malaysia. The simple random sampling of a total of 550 questionnaires distributed, where the researcher was able to collect about 506 completed forms or 92% rate of return that was later analysed. The research findings suggested that training and development is most significant and dominant dimension of HR system. Whereas organizational culture is confirmed to be the significant dimension of organisational development. Based on the Re-Specified model of organization management, results also showed that Human Resource system has a direct significant effect on employees' performance as compared to Organizational Development. It is found a non-significant influence of model on the performance of employees, which is driven to review the organization management strategy by the managers, executives and professionals. The research contributes with the sustainable enhancement of organizational performance model while driving for purpose driven work, rewards, work-life flexibility, among the generation Y workforce.The organization management for the generation Y performance reflects the general readers and specific stakeholders to implement the performance, engagement and retention in any organization. The research findings are relevant for the multidimensional stakeholders those are required towards the development of policy frameworks based on the validation of results from PLS-SEM model. The analytics and data interpretation extends the organizational decision-making process while supporting the efficient experience of generation Y workforce that must be part of organizations. The review of HR policies for the organizations is indicating through this research which can better demonstrate the value of consistent training to organize the smooth environment and development of the workplace.
Keywords: 650; Management; organization; performance; strategy; sustainability